Yoga Practitioners Uniquely Activate the Superior Parietal Lobule and Supramarginal Gyrus During Emotion Regulation - Wadden, Katie P.; Snow, Nicholas J.; Sande, Peder; Slawson, Sian; Waller, Tom; Boyd, Lara A. (Frontiers in Integrative Neuroscience, 2018)
Chronic stress contributes to both mental and physical illness. A high prevalence and cost of stress-related illnesses North America warrants investigation into alternative or complementary therapies which may help reduce adverse reactions to stressful stimuli. Emotion regulation is the process of monitoring and adjusting emotional responses to environmental stimuli and stressors. Individuals who participate in physical activity are less likely to have adverse responses to potentially stressful situations, potentially due to adaptions in emotion regulation. Yoga is a form of physical activity involving stretching exercises and meditation, that may lessen individuals’ levels of stress and anxiety and improve emotion regulation. High-frequency heart rate variability (HF-HRV) is considered a measure of parasympathetic nervous system (PNS) activity during the emotion regulation. Measuring HRV and brain activity using functional magnetic resonance imaging (fMRI) offers a useful, noninvasive approach to evaluating “neurovisceral” components of emotion regulation. We aimed to determine whether yoga practitioners (YP) exhibit different patterns of brain activation compared to recreational athletes (RA) without current yoga experience, while viewing emotionally arousing visual stimuli. Our secondary aim was to examine potential differences across groups in HRV throughout the presentation of these stimuli. Analysis of fMRI data during exposure to emotion-evoking (EE) stimuli revealed that the YP group activated two unique brain areas, namely the superior parietal lobule and the supramarginal gyrus. These areas have been associated with attentional awareness and reduced egocentric bias, processes that have been implicated in emotion regulation by others. The RA group activated the inferior middle frontal cortex, an area associated with cognitive reappraisal during emotion regulation. The YP group also demonstrated a trend towards a higher ratio of low- to high-frequency HRV compared to the RA group. The present findings support the presence of experience-dependent neurovisceral mechanisms associated with emotion regulation. Individuals who practice yoga regulate their neurovisceral responses to potentially stressful external stimuli in a different manner than recreational athletes who do not engage in yoga practice. The present study had a small sample size (RA: n = 12; YP: n = 19), which should be taken into account when interpreting the results.